Cybersecurity and Fintech Studies in Academic Discussion - Maliha, Hasna (Journal of Islamic Economics Literatures, 2024)
This study aims to see the development of research on the topic of "Cybersecurity and Fintech" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Cybersecurity and Fintech" which comes from the Dimension database with a total of 351 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Cybersecurity and Fintech" research development in the world. The results of the study found that there were 5 clusters with the most used words being security, system, company, model, threat, innovation, regulation, financial inclusion, banking, market, and cryptocurrency. Then, the research path topics related to Cybersecurity and Fintech are Data Security in Fintech Adoption, Big Data for Cybercrime Mitigation in Fintech, Information Security in the Fintech Ecosystem, Fintech cloud innovation for security, and Technological Innovation in Financial Markets.